Digital Management and Transformational Leadership in Educational Institutions - Kustomo Kustomo (Global Education : International Journal of Educational Sciences and Languages, 2025)
This study explores the role of transformational leadership in driving digital innovation and management practices in SMP Negeri 4 Jombang, an Indonesian public junior high school navigating the shift toward digital-based education. The research was motivated by the challenges many schools face in adopting digital technologies, particularly in terms of limited resources, digital literacy, and leadership readiness. The objective of this study is to investigate how school leadership contributes to the successful implementation of digital transformation, focusing on collaboration, inclusivity, and innovation within school management. Using a qualitative approach, the study involved in-depth interviews and observations with the school principal and several teachers as key informants. Data were analyzed thematically to capture leadership strategies, teacher engagement, and institutional responses to technological change. The findings reveal three main insights. First, the principal’s transformational leadership acts as the primary catalyst for digital innovation, inspiring a shared vision, fostering trust, and encouraging a proactive culture among teachers. Second, the implementation of digital management is characterized by collaborative decision-making and teacher inclusivity, ensuring that policies and practices remain contextually relevant and broadly accepted. Third, significant barriers persist, particularly regarding insufficient technological infrastructure, inconsistent internet connectivity, and varying levels of digital literacy among staff, which often limit the pace and scale of digital adoption. These findings suggest that effective digital transformation in education requires not only strong visionary leadership but also collective engagement from teachers and systemic support from educational stakeholders. The study emphasizes the importance of aligning leadership practices with institutional readiness to create sustainable digital change. By offering a practical framework that highlights the interdependence of leadership vision, collaborative practices, and organizational capacity, this research contributes to the growing literature on educational leadership and digital innovation. Furthermore, it provides valuable implications for policymakers and practitioners seeking to strengthen school management practices in the era of digital transformation.